RELATIONSHIP OF EXPLOSIVE MUSCLE MUSCLE TOWARDS DRIBBLING SKILLS IN FUTSAL GAME IN DEHASEN ACADEMY - Yogi Angga Putra; Arifto Juniardi (Hanoman Journal: Physical Education and Sport, 2020)
Based on the observations on the implementation of activities at the Academy of Dehasen club, the dribbling skills of the athletes were not good enough to cause the ball to go out of control. This problem is allegedly due to several factors, including the low levels of leg muscle explosive power of the athletes. This study aims to determine the correlation between leg muscle explosion power on dribbling skills. This research method is a correlational method. The population of this study were 25 Dehasen Futsal Club players, while the samples were taken in total sampling. This research was conducted at Unived futsal field in April 2019. Explosive power of leg muscles data were taken by vertical jump test, and the data of dribbling were taken through dribbling test. The data analysis technique used was a technique of correlation analysis. The results of the data analysis show that: There is a significant correlation between leg muscle explosive power (X) on dribbling skills in futsal athletes in the Academy of Dehasen University of Bengkulu, with rxy = 0.93 r (0.05) (19) = 0.396.